Consumer Purchase Decision and Brand Image Analysis Through Product Quality and Price: Study Case Frozen Pastry in Jakarta - Indonesia - Mumin, Adhi Trirachmadi; Ingkadijaya, Rahmat; Jason, Jason; Muhardiansyah, Doni; Wulan, Saptarining (Jurnal Penelitian Pariwisata, 2024)
The study investigates the effects of product quality and price on the purchasing decisions of Bonpatis Danish pastry sheets, with brand image acting as a mediator. Indonesia's food and beverage industry, mainly retail, is experiencing significant growth as modern retailers like Hypermart introduce competitive products. A quantitative approach was used, applying Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to data collected from 83 respondents, mainly Hypermart bakery employees in DKI Jakarta. Results indicate that product quality and price positively influence brand image and purchasing decisions. Specifically, product quality boosts brand image and directly affects purchase decisions, whereas price influences purchase decisions directly but not via brand image. The study emphasizes the role of product appearance and packaging in shaping brand perceptions and suggests improving these elements to attract more consumers. Due to a limited sample size, the study recommends future research to explore broader aspects like customer satisfaction and loyalty. Keywords: Danish pastry sheet, product quality, price, brand image, purchase decision.